Identifying the key factors of sustainable entrepreneurship in the Nigerian food industry: The role of media availability - Barnabas Nuhu Yakubu; Salamzadeh Aidin; Parisa Bouzari; Pejman Ebrahimi; Maria Fekete-Farkas (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The article's objective is to identify how media could facilitate the effect of sustainable entrepreneurship on consumer purchase behaviour, based on evidence from the food industry in Nigeria. Research Design & Methods: The research population was experts who have sufficient information, expertise, and experience in the field of sustainable entrepreneurship and marketing, and pay attention to online social platforms and consumer purchase behaviour. There population amounted to 33 interviewed experts. A combination of Delphi-ANP (Analytic Network Process) approaches was used. Results showed that customers' satisfaction was the key dimension that affects sustainable entrepreneurship in the Nigerian food industry. Findings: 'Access to the internet' had the highest rank (F15) (0.33741), which showed that it was the most important factor in developing sustainable entrepreneurship of food industry, regarding to media role in Nigeria. 'production process and the environment' (F1) (0.33461) ranked second and was close to the 'price satisfaction' (F17) (0.32049) in importance. In addition, managers should not ignore the 'excellent functional quality of the brand,' 'personal attributes of customers' care' and 'packaging quality,' since these three factors were ranked fourth, fifth and sixth, respectively. Implications & Recommendations: The entrepreneurs should focus more on this dimension to develop a sustainable food industry in Nigeria. Meanwhile, media availability had a significant role in developing sustainable entrepreneurship in Nigeria. Contribution & Value Added: Most researchers focused on sustainable entrepreneurship without considering the impacts of media as a channel of achieving it by changing the consumers' behaviours towards consuming a particular product. Therefore, this research -investigated how media could moderate the effect of sustainable entrepreneurship on consumer purchase behaviour, taking evidence from the food industry in Nigeria.
Keywords: L26; L82; L66; 330; Sustainable entrepreneurship; Media availability; Delphi approach; Analytic network process; Food industry